PERLINDUNGAN HUKUM PENCIPTA LAGU TERHADAP PEMBAJAKAN YANG DILAKUKAN MELALUI WEBSITE PENYEDIA JASA DOWNLOAD LAGU GRATIS DALAM MEDIA INTERNET - Arif, Moh Fauzan (Jurnal Ilmu Hukum Lasadindi, 2024)
Copyright infringement of songs via the internet, in this case illegal downloading, is currently still hotly discussed. Due to the government’s move to block several sites that provide free song download services, they can still be used by the general public. This of course raises the idea that what the government has done has not reached its maximum point in dealing with the problem of illegal downloading. So, this is what makes musicians very irritated by the government’s attitude of not paying attention and even considering not appreciating the creative works of the nation’s children. The aim of this research is to find out and explain the legal protection provided by the government to songwriters in dealing with act of copyright infringement in cyberspace, and to know and understand the responsibilities of free song download service providers for copyright violations via internet media. Based on the research results, it is understood that the legal protection provided by the government to songwriters in dealing with acts of copyright infringement in cyberspace is: firstly, blocking sites that are deemed to have violated copyright even though they are not operating optimally and do not reduce the occurrence of violations, and secondly carrying out socialization both to songwriters or rights holders about the importance of registering creations, as well as to the public about the culture of respecting the work of the nation’s children so that intellectual property rights law enfocement can be implemented properly. The response of free song download service providers to copyright violations via the internet is: not in accordance with the law, illegal site providers even deny their existance as illegal sites by promoting themselves as song search sites that do not upload songs. This site instead equates the site with search sites such as Google and Ymail.system. ABSTRAK Pelanggaran hak cipta atas lagu melalui media internet dalam hal ini illegal downloading, saat ini masih hangat diperbincangkan. Dikarenakan langkah pemerintah untuk memblokir beberapa situs yang menyediakan jasa download lagu secara gratis saat ini masih dapat dipergunakan oleh khalayak masyarakat. Hal ini tentu saja menimbulkan pemikiran bahwa apa yang dilakukan oleh pemerintah belum mencapai titik maksimal untuk menangani masalah illegal downloading ini. Sehingga, hal inilah yang membuat para musisi sangat gerah terhadap sikap pemerintah yang tidak memperhatikan bahkan menganggap tidak menghargai hasil karya cipta anak bangsa. Tujuan penelitian ini untuk mengetahui dan menjelaskan perlindungan hukum yang diberikan pemerintah kepada pencipta lagu dalam mengatasi tindakan pelanggaran hak cipta di dunia maya, dan untuk mengetahui dan memahami pertanggung jawaban pihak penyedia jasa download lagu gratis terhadap pelanggaran hak cipta melalui media internet. Meskipun terdapat perbedaan dalam detail penerapannya, tujuan utama dari semua instrumen hukum ini adalah untuk memberikan perlindungan yang efektif bagi hak merek, memastikan penegakan hukum yang adil, dan mendukung perdagangan yang transparan dan adil. Harmonisasi hukum nasional dengan standar internasional ini memainkan peran penting dalam memfasilitasi perlindungan kekayaan intelektual yang lebih baik dan meningkatkan kepercayaan dalam sistem perdagangan global